ROM And CIMT Treatment Effects To Stroke Patients’s Upper Extremity Functional Ability - Cintia Tri Wulandari; Sulastyawati Sulastyawati; Lingling Marinda Palupi (Alma Ata University Press, 2020)
Stroke is a brain functionality disorder caused by disruption of blood supply into the brain. Stroke is one of the leading causes of weakness or hemiparesis on ekstremities. A stroke patient who encounter hemiparesis may suffer joints contracture which then can become permanently disabled if it is not trained. In hospitals, Range of Motion Exercise is often performed, but the results are less optimal. This research aims to discover the combination effects of Range of Motion Exercise (ROM) and Constraint Induced Movement Therapy (CIMT) to the changes of upper extremity functional ability by using a measuring tool Chedoke Arm and Hand Activity Inventory form (CAHAI) to stroke patients with hemiparesis at Interna 1 of dr. R. Soedarsono Regional Public Hospital, Pasuruan. This research uses Quasi Experimental with non-Equivalent Control Group design. The respondents were chosen by using Consecutive Sampling technique with a total of 34 respondents divided into two groups. 17 respondents as the treatment group were given combination therapy of ROM and CIMT and 17 respondents as control group were given ROM therapy only..The Statistical test was done by using Paired T-test and Independent T-test. According to the result of Paired T-test, there are differences found in the result of upper extremity functional ability after the combination intervention of ROM and CIMT had been given in the treatment group with P Value 0.000 (p < 0.05). Then, the independent t-test stated that the intervention of ROM and CIMT hold an influence to upper extremity functional ability with P Value = 0.047 (p < 0.05). This research concludes that the combination of Range of Motion Exercise (ROM) and Constraint Induced Movement Therapy (CIMT) can increase the upper extremity functional ability so that it can be used as an alternative of exercise therapy to increase the upper extremity functional ability of stroke patients.